Pengaruh Pembelajaran Fonetik terhadap Persepsi Siswa dalam Pembelajaran Bahasa Arab: Studi Kasus Kesalahan Pelafalan Huruf Arab - Laili Mas Ulliyah Hasan; Muhammad Rido'i (Institut Agama Islam Negeri Syaikh Abdurrahman Siddik Bangka Belitung, 2024)
This study explores the impact of phonetic teaching on the perception of fifth-grade students Madrasah Ibtidaiyah Miftahul Ulum Al Ghazali Paterongan Galis Bangkalan in learning Arabic, focusing on the mispronunciation of Arabic letters. It was found that the lack of attention from teachers to the correct sounds of Arabic letters led to pronunciation errors among students. The research methods included classroom observation, interviews with teachers and students, and phonetic tests. The results showed that students who received more focused phonetic instruction exhibited significant improvement in the pronunciation of Arabic letters. Students taught with proper phonetic methods were better able to distinguish and pronounce Arabic letters correctly compared to those who did not receive adequate phonetic instruction. The conclusions of this study emphasize the importance of correct phonetic teaching in the Arabic learning process to reduce pronunciation errors and enhance student fluency. Recommendations for teaching practices include teacher training in Arabic phonetics and integrating phonetic methods into the learning curriculum.